King penguin ornamentation and acoustics - Kriesell, Hannah Joy; Aubin, Thierry; Planas-Bielsa, Victor; Schull, Quentin; Bonadonna, Francesco; Cornec, Clément; Le Maho, Yvon; Troudet, Laura; Le Bohec, Céline (PANGAEA, 2021)
King penguins are sexually monomorphically ornamented seabirds that perform a complex visual and acoustic courtship display. Coloured beak spots and ear patches contain information about the condition and physiological status of adult males and females, but their role as a signal of age has previously only been studied in young birds. Vocalizations have mainly been studied as signals of individuality and not in the context of courtship. We investigate two multicomponent signals in the context of mate choice by analysing beak spot, ear patch, and call parameters of wild king penguins. We explore the relation between those signals and age as well as age-classes (chicks, juveniles, adults). Ornament parameters were weakly correlated to continuous age in males, but not in females, while acoustic parameters were highly correlated to continuous age in both sexes. The calls' fundamental frequency and energy parameters, and all the beak spot parameters reliably classified individuals into their age-class. Since age-class was redundantly encoded in both acoustic and colour parameters, we hypothesize that calls and ornaments function as back-up signals that increase the chance of accurately conveying the age-class of the sender to receivers. King penguins might sequentially analyse age-class signals during courtship, where acoustic signals serve as long-range communication when sender and receiver are out of sight, and ornamentation signals become important at close range. We show the importance of considering bimodal, multicomponent signals when studying complex behaviour and discuss how signalling environment, the species' life-history and mating system influence the evolution of communication signals.
Keywords: Animal communication; Mate choice; Optimal response index; Ornamentation; Ornamentation; Penguin; Sexual Maturation; Vocalisations